Analisis Hukum Ekonomi Syariah atas Sistem Fee Akad Wakalah Jual Beli Rumah di Kelurahan Way Laga Sukabumi Bandar Lampung: Analysis of Sharia Economic Law on the Wakalah Contract Fee System for Buying and Selling Houses in Way Laga Village Sukabumi Bandar Lampung) - Arnis Arbella; Badruzaman; Helma Maraliza (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2026)
The practice of the fee system in the wakalah (house purchase and sale) contract in Way Laga Village covers the payment mechanism (2% or IDR 6 million of the IDR 300 million price), payment timing (upfront), the form of agreement (verbal), and the duties of the representative. This study also analyzes the perspectives of Islamic economic law on the implementation of the fee system, including its compliance with the pillars of wakalah bil ujrah (contractual agreement), the principle of ujrah (indebtedness), the potential for gharar (unlawful agreement), the trustworthiness of wakalah (indebtedness), and the principle of justice. This research also involves an in-depth study from an Islamic economic legal perspective regarding the validity of this mechanism and the possibility of violations. The method used was a qualitative field-based approach with a descriptive analytical approach. Primary data were collected through in-depth interviews with parties directly involved in the transaction. The data was then processed through editing, coding, and structured grouping using inductive analysis based on field findings and guided by the principles of Islamic jurisprudence (fikih muamalah). The results indicate that the practice of fee payments is carried out verbally without a clear, legally binding written contract. The fee is paid by the muwakil to the agent before the transaction is completed, thus violating the principle of the agent's trust, creating elements of gharar (uncertainty), tadlis (false statements of facts), and raising fundamental doubts about the validity of the wakalah contract as a whole. A serious problem arises if the agent fails to fulfill his duties within 5 months, as his duties are rendered ineffective even though the fee was paid in advance by the muwakil before the house was sold.